Secular trend of head and face shape in adult population of Vojvodina (Serbia) - Tatjana M. Pavlica; Rada S. Rakić; Verica S. Božić-Krstić; Biljana Đ. Srdić-Galić (Taylor & Francis Group, 2018)
Background: Different populations show variation in the pattern of change in craniofacial dimensions over time. Earlier studies of craniofacial traits in the Republic of Serbia were carried out, without any particular reference to secular changes. Aim: The aim of the study is to determine possible changes in craniofacial dimensions among the adult population of Vojvodina (Serbia) during a 33 year period. Subjects and methods: The findings of the study are based on the comparison of data from two cross-sectional surveys. The earlier research was conducted in 1975 (n = 2600) and the second from 2001-2006 (n = 4504). Four craniofacial dimensions and body height were analysed. Results: In terms of the head dimensions, head length in males has increased substantially, while head breadth has decreased in both sexes. The total change in the cephalic index is 0.58 (males) and 0.48 (females) units per decade. Morphological face height has substantially increased, while face breadth has decreased in both sexes over this period. The total change in the facial index per decade is 0.75 units in males and 0.98 in females. Conclusion: The results point to a trend of head and face shape remodelling toward a narrower head and more elongated face, consistent with ongoing dolichocephalisation.